The Philosophy of Education Reviewed from the Perspective of Hadith - Aliadi, Aliadi; Husti, Ilyas; Nurhadi, Nurhadi (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
The purpose of this research is to find out the radicalization of philosophy in relation to the hadith of the Prophet Muhammad. The study of this research uses a literature review taken in accordance with the subject matter and analyzed in depth so that conclusions and findings can be drawn. Literature taken from books, journal articles both national and international. The results of this study are Radicalization of philosophy is an effort to explore ideas or realities to their roots contained in hadith related to education and its implementation in modern Islamic education. In the realm of philosophy, radical thinking also means understanding something to the root of the problem, by always being critical and analytical in addressing various phenomena.  Radicalization of Philosophy in Hadith is the understanding of Hadith that gives birth to various implications both concept of education.